A comparison between tourniquet application and epinephrine injection for hemostasis during hypospadias surgery: The effect on bleeding and postoperative outcome. Issue 3 (June 2016) - Alizadeh, F.; Fakoor, A.; Haghdani, S.
Summary: Objective: To compare tourniquet application and epinephrine injection for hemostasis during hypospadias surgery in terms of bleeding and complications. Methods: Between April 2013 and September 2014, patients who were admitted for hypospadias repair were divided by random allocation into either a diluted epinephrine injection (DE) group or tourniquet application (T) group for hemostasis during the procedure. In the T group, a rubber band was applied at the base of the penis after skin dissection, and in the DE group, epinephrine 1/100, 000 was injected along the incision lines. The patients' ages, urethral defect lengths, pre-operative, intraoperative and postoperative variables were compared between the two groups. Results: A total of 70 patients (35 in each group) were enrolled into the study. The mean ages and preoperative variables were not significantly different. Average blood loss was 23.51 ± 15.36 cc in the tourniquet group and 15.99 ± 10.00 cc in the epinephrine group, and was significantly higher in tourniquet group ( P  = 0.022); however, the mean operative time was not significantly different. Postoperative complications, described as Clavian classification, were reported in eight patients (23%) in the T group and 10 patients (30%) in the DE group, which was not significantly different. Conclusion: Epinephrine injections minimize operative bleeding without significant harmful effects on postoperative outcomes; therefore, it could be considered to be a safe and effective method for preparation of a bloodless field during hypospadias surgery.